2014
DOI: 10.3171/2014.4.jns13789
|View full text |Cite
|
Sign up to set email alerts
|

Survival after surgery and stereotactic radiosurgery for patients with multiple intracranial metastases: results of a single-center retrospective study

Abstract: Object Patients with systemic cancer and a single brain metastasis who undergo treatment with resection plus radiotherapy live longer and have a better quality of life than those treated with radiotherapy alone. Historically, whole-brain radiotherapy (WBRT) has been the mainstay of radiation therapy; however, it is associated with significant delayed neurocognitive sequelae. In this study, the authors looked at survival in patients with single and multiple intracranial metastases who had undergone surgery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…Breast cancer metastases have been shown to have a particularly high rate of LMD [3234]. Additionally, many studies reported on the adverse side effects of WBRT, including physical symptoms such as alopecia, somnolence, hearing loss, skin changes, and neurocognitive decline, manifested as memory loss and learning impairment [2, 7, 18, 26]. In particular, the cognitive decline following WBRT has been linked to leukoencephalopathy, which is supported by the increased risk for leukoencephalopathy in patients receiving post-operative WBRT [20, 35] Another study, evaluating 59 patients treated with primary SRS, found that even after multiple courses of SRS, quality of life (QOL), measured with the EQ-5D instrument, was preserved in 77% of patients at 12 month follow-up [36].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Breast cancer metastases have been shown to have a particularly high rate of LMD [3234]. Additionally, many studies reported on the adverse side effects of WBRT, including physical symptoms such as alopecia, somnolence, hearing loss, skin changes, and neurocognitive decline, manifested as memory loss and learning impairment [2, 7, 18, 26]. In particular, the cognitive decline following WBRT has been linked to leukoencephalopathy, which is supported by the increased risk for leukoencephalopathy in patients receiving post-operative WBRT [20, 35] Another study, evaluating 59 patients treated with primary SRS, found that even after multiple courses of SRS, quality of life (QOL), measured with the EQ-5D instrument, was preserved in 77% of patients at 12 month follow-up [36].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 20–40% of cancer patients with primary extracranial cancer will develop brain metastases during the course of their disease [6]. In the United States alone, this represents about 98,000 to 170,000 new diagnoses each year [6, 7]. Median survival without treatment is estimated at 1 month, and increases to 3–12 months when cranial radiation therapy is used [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations